One and Five Ideas : On Conceptual Art and Conceptualism - Smith, Terry (Terry E.) (Book collections on Project MUSE., 2017)
The eminent critic, historian, and former member of the Art & Language collective Terry Smith explores the artistic, philosophical, political, and geographical dimensions of conceptual art and conceptualism while offering a theory of contemporary art.